'Our life is pointless … ': Exploring discrimination, violence and mental health challenges among sexual and gender minorities from Brazil. Issue 10 (2nd October 2020) - Malta, Monica; Gomes de Jesus, Jaqueline; LeGrand, Sara; Seixas, Michele; Benevides, Bruna; Silva, Maria das Dores; Lana, Jonas Soares; Huynh, Hy V.; Belden, Charles M.; Whetten, Kathryn
ABSTRACT: Worldwide, Brazil has the highest prevalence of violence and hate crimes against sexual and gender minorities (SGMs) among countries with available data. To explore the impact of this scenario, we conducted a qualitative study with 50 SGMs from Rio de Janeiro, Brazil. Among the participants, 66% screened positive for generalised anxiety disorder, 46% for major depressive disorder and 39% for PTSD. A third reported low self-esteem (32%) and one quarter low social support (26%). Experiences of interpersonal discrimination were highly prevalent (>60%), while institutional discrimination related to employment or healthcare was reported by 46% of participants. Verbal abuse is very common (80%), followed by physical assault (40%). Sexual violence is highly frequent among women. Focus groups analysis highlighted three major domains: (1) stigma and discrimination (family, friends and partners, in schools and health services, influencing social isolation); (2) violence (bullying, harassment, physical and sexual violence); and (3) mental suffering (alcohol and drug abuse, depression, suicidality, anxiety). Our findings suggest a close synergy between experiences of discrimination and violence with selected mental disorders. This complex synergy might be better addressed by longer-term individual and group-level interventions that could foster social solidarity among the different groups that comprise SGMs.